2019
DOI: 10.1186/s12909-019-1912-4
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ resilience: a protective role on stress and quality of life in clerkship

Abstract: BackgroundResilience refers to the ability to be flexible and adaptive in response to challenges. Medical students in clerkship who are transitioning from medical studies to clinical practice face a variety of workplace demands that can lead to negative learning experiences and poor quality of life. This study explored whether medical students’ resilience plays a protective role against the stresses incurred during workplace training and on their professional quality of life during clerkships.MethodsThis was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 47 publications
6
53
0
4
Order By: Relevance
“…28 29 Further, it has been shown that resilience is related to reduced burnout and increased satisfaction in medical students. 30 The findings of this study corroborate the conceptual framework of resilience. Those students who felt supported by and who had confidence in their university had lower levels of reported stress.…”
Section: Original Researchsupporting
confidence: 79%
“…28 29 Further, it has been shown that resilience is related to reduced burnout and increased satisfaction in medical students. 30 The findings of this study corroborate the conceptual framework of resilience. Those students who felt supported by and who had confidence in their university had lower levels of reported stress.…”
Section: Original Researchsupporting
confidence: 79%
“…In addition to a substantial workload, medical students and residents are confronted with a wide range of stressors including inflexible work schedules, sleep deprivation, fatigue, time-consuming clerical and administrative responsibilities, insufficient access to allied health personnel and staff (e.g., nurses, social workers), and unwelcoming learning environments [1]. Coupled with societal-and selfexpectations [2], medical students and residents are at high risk for compassion fatigue [3][4][5], low self-esteem [6], decreased mental health [7][8][9][10][11][12][13], and overall poor quality of life [14][15][16][17][18][19][20]. The implications of elevated psychological distress among medical students and residents are welldocumented and include diminished academic accomplishment [21,22], substance abuse [9,[23][24][25], decreased empathy [26,27], increased professional misconduct [28], and suicide [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the increasing demand for clinical training, along with new concerns and responsibilities of students during such academic levels. A recent study highlighted several stressful situations like using psychometric skills, applying clinical knowledge in real-life situations, trauma exposure, understanding the role and regulating of clinical settings during their clerkship [29]. Lin et al argued that medical students, as novices in medical practice, experience greater physical demands resulting from their lack of efficiency or familiarity with the workload, leading to frustration in learning and reducing their compassion satisfaction [29].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study highlighted several stressful situations like using psychometric skills, applying clinical knowledge in real-life situations, trauma exposure, understanding the role and regulating of clinical settings during their clerkship [29]. Lin et al argued that medical students, as novices in medical practice, experience greater physical demands resulting from their lack of efficiency or familiarity with the workload, leading to frustration in learning and reducing their compassion satisfaction [29]. Therefore, understanding of clinical learning process along with essential supervision by clinicians in various disciplines might lead to a stress-free learning environment for our students in patient care and hospital setting.…”
Section: Discussionmentioning
confidence: 99%